Exploring barriers of cardiovascular disease prevention among women with hypercholesterolemia - Samsudin, Suhaiza; Md Aris, Mohd Aznan; Abdullah, Fa’iza; Mohd Arifin, Siti Roshaidai (Science and Engineering Research Support Society, 2020)
Introduction: Hypercholesterolemia is one of major risk factors that contribute to the development of cardiovascular diseases (CVD). The previous study showed that the prevalence of hypercholesterolemia had an increasing trend among women as compared to men. Therefore, the main objective of this study was to explore the barriers and challenges faced by women with hypercholesterolemia in the prevention of CVD risk factors. Methodology: A qualitative study was designed to explore and understand the barriers for CVD prevention among women with high cholesterol level. A total of 13 women with hypercholesterolemia in their blood were detected during a routine medical screening by a primary health care clinic at the International Islamic University Malaysia, in Kuantan, Pahang. The women were interviewed. All interviews were audio recorded, transcribed, coded and analysed by using NVIVO Version 12 software. Findings: Five barriers were identified and divided into two categories, namely personal barrier (time-related barrier, lack of support, poor motivation and misconception) and environmental barrier (lack of accessibility to healthy food). Conclusion: This study highlighted women’s perceptions on barriers that influence their abilities to prevent cardiovascular risk factors. Consequently, intervention strategies were proposed to address CVD risk and overcome the barriers.